Iowa Birdline update, February 4, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of the Iowa Birdline update for February 4, 1991. Highlights include reports of owls, swans and eagles. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed